Hydrogen Sulfide Inhibits High Glucose-Induced Neuronal Senescence by Improving Autophagic Flux via Up-regulation of SIRT1 - Wu, Lei; Chen, Ying; Wang, Chun-Yan; Tang, Yi-Yun; Huang, Hong-Lin; Kang, Xuan; Li, Xiang; Xie, Yu-Rong; Tang, Xiao-Qing (Frontiers in Molecular Neuroscience, 2019)
Hyperglycemia, a key characteristic and risk factor for diabetes mellitus (DM), causes neuronal senescence. Hydrogen sulfide (H2S) is a novel neuroprotectant. The present work was to investigate the potential effect of H2S on hyperglycemia-induced neuronal senescence and the underlying mechanisms. We found that NaHS, a donor of H2S, inhibited high glucose (HG)-induced cellular senescence in HT22 cells (an immortalized mouse hippocampal cell line), as evidenced by decrease in the number of SA-β-gal positive cells, increase in the cells growth, and down-regulations of senescence mark proteins, p16INK4a and p21CIP1. NaHS improved the autophagic flux, which is judged by decrease in the amount of intracellular autophagosome as well as up-regulations of LC3II/I and P62 in HG-exposed HT22 cells. Furthermore, blocked autophagic flux by chloroquine (CQ) significantly abolished NaHS-exerted improvement in the autophagic flux and suppression in the cellular senescence of GH-exposed HT22 cells, which indicated that H2S antagonizes HG-induced neuronal senescence by promoting autophagic flux. We also found that NaHS up-regulated the expression of silent mating type information regulation 2 homolog 1 (SIRT1), an important anti-aging protein, in HG-exposed HT22 cells. Furthermore, inhibition of SIRT1 by sirtinol reversed the protection of H2S against HG-induced autophagic flux blockade and cellular senescence in HT22 cells. These data indicated that H2S protects HT22 cells against HG-induced cellular senescence by improving autophagic flux via up-regulation of SIRT1, suggesting H2S as a potential treatment strategy for hyperglycemia-induced neuronal senescence and neurotoxicity.